Questioning the spatial association between the spread of COVID-19 and transit usage in Italy - Mattia Borsati; Silvio Nocera; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2020)
Within the much broader framework of global interest, the dilemma concerning the real impact of mode of transport on the spread of COVID-19 has been a priority for transport stakeholders and policy-makers. How dangerous is it to move around a certain territory? Does the danger depend on the mode of transport? By considering a novel and detailed dataset at the level of local labour markets, we analysed the spatial association between the propensity to use public transport and excess mortality in Italy attributable to the spread of COVID-19. We found that places characterised by larger commuting flows exhibit higher excess mortality, but observed no significant spatial association between excess mortality and transit usage. Our results were obtained by considering a wide range of heterogeneity in the estimation of quantile regressions across a variety of specifications. Although we do not provide a definitive answer concerning the risk associated with transit use, our analysis suggests that mobility, not modal choice, should be considered a main driver of the contagion.
Keywords: H41; I18; J61; R41; 330; COVID-19; Public transport; Commuting; Quantile regression; Italy